Examining Tradition and the Current State of Education Innovation in Contemporary Indonesia: Challenges of a Middle Eastern University Alumni Kyai in an Islamic Boarding School - Kinoshita, Hiroko (Journal of Asian Islamic Educational Management (JAIEM), 2023)
This research focuses on the activities of a young kyai who seeks to provide education, informed by his experience of studying in the Middle East at a pondok pesantren, an Islamic boarding school, in contemporary Indonesia. This study is an analysis derived from fieldwork that focused primarily on qualitative interviews and the author's own observations while residing at one of the pesantren in East Java. Since inheriting the pesantren at a young age, the kyai have incorporated the study of languages such as English and Arabic alongside the continuation of the traditional Islamic book, kitab learning. Furthermore, it has become apparent that in the context of the diversifying landscape of pesantren education, the kyai is striving to cultivate boarding students, santri with a broad perspective, even though they are in a rural area, by sharing the knowledge gained from studying in the Middle East and advocating for a committed approach to learning.